2005
DOI: 10.1097/01.ogx.0000183603.37714.78
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Remission Following Withdrawal of Dopamine Agonist Therapy in Subjects With Microprolactinomas

Abstract: The Fibroid Registry for Outcomes Data (FIBROID) was founded in 1999 to serve as a prospective multicenter database of women undergoing uterine embolization for leiomyomata. This paper presents an analysis of the short-term outcomes of patients enrolled at 72 participating sites. Of a total 3005 patients, 2729 had a 30-day follow-up interview, which provided information on any further medical care, adverse events, time to return to work, and time to return to normal activities. The Registry defined an adverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 0 publications
0
20
0
2
Order By: Relevance
“…Withdrawal from CAB treatment, which is known to be superior to bromocriptine, 2,4,7,9,12,13 was followed by remission of hyperprolactinaemia in 22 -31% of patients. 8,10,29,31 More recently, we reported an estimated hyperprolactinaemia recurrence rate of 24% in NTH, 32·6% in patients with micro-, and 43·3% in those with macroprolactinomas in carefully selected patients in 2-5 years after CAB withdrawal. 19 Of clinical relevance, none of the patients experiencing recurrent hyperprolactinaemia showed tumour re-growth and only a minority noticed reappearance of symptoms of gonadal dysfunction.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Withdrawal from CAB treatment, which is known to be superior to bromocriptine, 2,4,7,9,12,13 was followed by remission of hyperprolactinaemia in 22 -31% of patients. 8,10,29,31 More recently, we reported an estimated hyperprolactinaemia recurrence rate of 24% in NTH, 32·6% in patients with micro-, and 43·3% in those with macroprolactinomas in carefully selected patients in 2-5 years after CAB withdrawal. 19 Of clinical relevance, none of the patients experiencing recurrent hyperprolactinaemia showed tumour re-growth and only a minority noticed reappearance of symptoms of gonadal dysfunction.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies investigating the results of withdrawal from bromocriptine treatment, mainly in patients with microprolactinomas or NTH, have reported remission rates ranging from very disappointing (< 10%) [20][21][22][23] to moderate (20 -44%). [24][25][26][27][28][29] The only study of exclusively patients with macroprolactinomas showed a remission rate of 8%. 30 High recurrence rates of hyperprolactinaemia were reported after treatment withdrawal of pergolide or quinagolide; 21,31 however, only a few patients have been studied with these two latter drugs.…”
Section: Discussionmentioning
confidence: 99%
“…11 Other studies have shown comparable recurrence rates to those that we demonstrate in our data: Cannavo and colleagues reported an 81AE5% recurrence rate at 1 year following DA withdrawal in unselected patients (n = 27) with both macroprolactinomas and microprolactinomas 18 ; Biswas and colleagues reported on 67 patients with microprolactinoma with a recurrence rate of 68AE7%. 19 Previously, in a retrospective study by Passos and colleagues on 131 patients with prolactinoma (62 with microprolactinoma and 69 with macroprolactinoma) who had achieved normalization of serum prolactin with bromocriptine, only 25AE8% of microprolactinomas and 15AE9% of macroprolactinomas persisted with normoprolactinaemia during a median of 44 months following bromocriptine withdrawal. 20 The five published studies on recurrence of hyperprolactinaemia following cabergoline withdrawal in patients with prolactinoma ( Table 2) show relatively high recurrence rates, comparable to our study.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is very important, as permanent remission is reported in only 7-44% of patients after discontinuation of the dopamine agonists bromocriptine and cabergoline. 8,32,34,35,[37][38][39][40] Only Colao et al . 41 reported a higher success rate of cases in which remission was avoided after discontinuation of cabergoline: 70% in microprolactinoma patients and 64% in macroprolactinoma patients.…”
Section: Discussionmentioning
confidence: 99%